Speech and language characteristics in Smith–Magenis syndrome: Case report - Garayzábal Heinze, Elena; Hidalgo de la Guía, Irene; Rosa, Kriscia Gobi [UNESP]; Giacheti, Célia Maria [UNESP]; Rossi, Natalia Freitas [UNESP] (Elsevier, 2021)
Smith–Magenis syndrome (SMS) is a rare neurodevelopmental disorder with mild-to-moderate intellectual disability. Speech and language impairments have not been well described as part of the SMS phenotype. This study reports the speech and language characteristics presented by a classical SMS case, a 20-year-old woman with positive deletion in the region 17p11.2. The case presented a borderline IQ on verbal and performance Wechsler scales. Language standardized tests (i.e., Peabody, Token test, CEG test and Boehm test) and naturalistic language sample (i.e. conversation and story generation) were used to assess speech and language performance. Speech characteristics included imprecise speech, with a high speech rate, hoarse voice, hypernasality and intelligibility deficits. The performance in all standardized tests was poor. Socio-communicative deficits included repetitive and persistent verbal behavior, difficulties in the use of linguistic strategies to repair communication breakdowns, limited vocabulary production and short overall length utterances with reduced grammatical components. The results contribute to expanding knowledge about the SMS phenotype, also to highlight the need to include speech and language evaluation as part of the clinical assessment of SMS and, at the same time, to draw attention to the need to include early communications skills in language intervention programs.
Características del habla y del lenguaje en el síndrome de Smith-Magenis: caso clínico
Keywords: Language; Smith–Magenis syndrome; Speech